Standardizing roles and responsibilities to improve efficiency of a regulatory compliance department in a power company - Montanez, Aila Marie C. (Animo Repository, 2022)
The Electric Power Industry in the country is mainly governed by the Republic Act No. 9136, or the Electric Power Industry Reform Act (EPIRA) of 2001. It established the division of the electric power industry into four segments: generation, transmission, distribution, and supply. As some of these segments are considered public utility, operating in the industry is heavily regulated and monitored. Hence, the importance of a Regulatory Compliance Department cannot be undermined. This research paper presents ways to improve a department's efficiency by standardizing roles and responsibilities. First-, second-, and third-person techniques were used to identify issues, create plans, take action, and evaluate the action. The action research used process maps and the RACI Matrix to delineate roles and identify areas for collaboration. The Kotter's 8 Step Change Model was used to implement these changes. After the implementation of two (2) research cycles, it was observed that the process maps and RACI matrix helped the Departments involved in identifying their roles for each compliance and requirement. There was also a raised sense of ownership, responsibility, and accountability from each Department. However, it was identified that management direction and support are vital for effective collaboration. Lastly, a new framework through a Venn diagram showing the independency of each Department and their overlapping roles was used to present a guide for similar organizations in establishing standardized roles and their opportunities for collaboration. Ideas and ways to create and embed a culture of collaborative teams within the organization were also identified.